Meet your competition data from the IRI R&D survey - Wolff, Michael F.
Michael F. Wolff reports that an analysis of corporate R&D spending at the business segment level confirms-among many other things-the shift to more product development and technical service.
Information on R&D spending and performance is available for the first time at the level of individual firm business segments.
Keywords: R&D survey